Maternal resistance to COVID-19 vaccination: Attitudes and knowledge in preschool children’s immunization - Ochoa-Beggazo, Roxana Belén; Huamán-Mayta, Justiniana; Chávez-Parillo, Jesús Roger; Prado-Espinoza, Azucena Natividad; Abarca-del-Carpio, Jacinta Mayrene (Edelweiss Applied Science and Technology, 2025)
Childhood immunization is a crucial public health measure, yet maternal resistance to COVID-19 vaccination for preschool-aged children remains a significant challenge. While prior research has explored general vaccine hesitancy, few studies have examined the direct relationship between maternal knowledge and attitudes regarding COVID-19 vaccination in this population. This study aims to analyze the reasons behind maternal vaccine hesitancy, assessing how knowledge gaps and attitudinal factors shape vaccination decisions. A mixed-methods approach was employed, collecting quantitative data through structured questionnaires and qualitative insights from semi-structured interviews with 140 mothers in Arequipa, Peru. Descriptive and correlational analyses were performed to identify key determinants of vaccine acceptance. Findings indicate that although most mothers adhere to routine immunization schedules, misinformation and concerns about vaccine safety contribute to hesitancy. A statistically significant correlation was found between maternal knowledge levels and positive vaccination attitudes. These results highlight the need for targeted educational campaigns and improved communication between healthcare providers and mothers. Future efforts should focus on addressing misinformation, reinforcing trust in vaccines, and implementing culturally adapted interventions. While this study provides critical insights, its non-probabilistic sampling limits generalizability, and further longitudinal research is required to track evolving attitudes over time.